The Nelson-Seiberg Theorem Generalized with Nonpolynomial Superpotentials - Zhengyi Li; Zheng Sun (Advances in High Energy Physics)
The Nelson-Seiberg theorem relates R-symmetries to F-term supersymmetry breaking and provides a guiding rule for new physics model building beyond the Standard Model. A revision of the theorem gives a necessary and sufficient condition to supersymmetry breaking in models with polynomial superpotentials. This work revisits the theorem to include models with nonpolynomial superpotentials. With a generic R-symmetric superpotential, a singularity at the origin of the field space implies both R-symmetry breaking and supersymmetry breaking. We give a generalized necessary and sufficient condition for supersymmetry breaking which applies to both perturbative and nonperturbative models.